Relationship between anxiety, loneliness, and sleep-disorders with social media addiction among adolescent - Sarfika, Rika; 'Alini, Zahratul; Refnandes, Randy; Wijaya, Nindi Eka; Saifudin, I Made Moh. Yanuar (Intelektual Pustaka Media Utama, 2024)
In the digital era, social media usage has become an integral part of daily life, particularly among adolescents. This study investigates the relationship between anxiety, loneliness, sleep disorders, and social media addiction among adolescents. A cross-sectional study involving 290 X and XI-grade students utilized standardized instruments: the Bergen Social Media Addiction Scale (BSMAS), Zung Self-Rating Anxiety Scale (SAS/SRAS), UCLA Loneliness Scale Version 3, and Pittsburgh Sleep Quality Index (PSQI). Bivariate analysis was conducted using the Chi-square test (p<0.05). Findings revealed 10.7% severe social media addiction, 21.4% severe anxiety, 4.8% significant loneliness, and 74.5% poor sleep quality. Significant associations were found between anxiety (p=0.013), loneliness (p=0.010), sleep disturbance (p=0.033), and social media addiction. Higher anxiety, loneliness, and poor sleep quality correlate with increased susceptibility to social media addiction among adolescents. This underscores the importance of addressing psychological well-being in interventions aimed at mitigating social media addiction.